GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA PUTRI TERHADAP KEPUTIHAN DI SMA NEGERI 2 PONTIANAK TAHUN 2013 - ., Ori Aprisia Putri (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Leucorrhea is a reproductive health problem that almost75% of women at all ages experienced, both physiological andpathological. The study show that 75% women worldwide sufferleucorrhea at least once in their life. Female adolescent is a group thathad susceptible to leucorrhea problem. Objective. The purpose of theresearch was to know the distribution of knowledge and attitude aboutleucorrhea in SMAN 2 pontianak on 2013. Metodology. This study was adescriptive observational study with cross-sectional design. The samplefor this study are 59 sample. Date were obtained trought quetionnaires.Result. Of the 59 sample obtained, 44 sample (74,6%) have highknowledge, 46 sample (78%) have positive attitude. Conclusion. It wasconcluded that sample have good knowledge and positive attitude. Thebetter knowledge of a person to an object that it will better the personattitude toward the object. Keywords : Knowledge, Attitude, Leucorrhea